Manejo de Brachiaria ruziziensis com uso de herbicidas na cultura da soja em sistema de plantio direto na savana da Roraima - Rodrigues, Guilherme Silva (2012)
The no-tillage system for soybean is an established practice in the Roraima savanna, but it has been presenting limitations mainly about the maintenance of soil covering, due to difficulties in the establishment of cover crops after harvest of annual crops due to the long period of water deficit. An alternative that has been recommended is to conduct the annual intercropped with the cover plant managed with the use of reduced herbicides doses, which favors the straw production after harvest of soybeans. The objective of this study was to evaluate the effect of desiccants and post-emergence herbicide doses on soil covered with Brachiaria ruziziensis, the yield components, productivity of soybean grain, and the incidence of weeds in a no-tillage system in the Roraima savanna. The experiment was conducted at Embrapa Roraima, Experimental Farm Água Boa, Boa Vista - RR in the period from May to November 2011. The experimental design was a randomized completely blocks in split plots with four repetitions. The treatments consisted in four doses of desiccants herbicide glyphosate (720, 1200, 1680, and 2160 g a.i. ha-1) and five doses of post- emergent herbicide fenoxaprop-p-ethyl (0, 38.5, 77, 115 5, 154 g a.i. ha-1). The results were submitted to variance analysis (p <0.05) and when signi.ficant were submitted to regression analysis. It was verified for the soybean crop only effect of glyphosate doses, where the lowest dose of the desiccant decrease the number of pods per plant, the number of grains per pod and grain productivity. The maximum productivity (3660 kg ha-1) was obtained with 1387.64 g a.i. ha-1of glphosate. The yield of fresh and dry weight of Brachiaria ruziziensis at 70 days after soybean harvest decreased with the dose increase of glyphosate in desiccation and fenoxaprop-p-ethyl in post-emergence. Weeds, due to the suppression of brachiaria grass, increase the plant population with the increase of glyphosate doses. The dose of 1200 g a.i. ha-1 of glyphosate promotes soybean yield, fresh and dry weight of Brachiaria ruziziensis favorable to the production of forage and straw to the no-tillage system.